APEC dan Proses Integrasi Ekonomi Regional di Kawasan Asia Pasifik - Sigit Aris Prasetyo (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2011)
Economic regionalism has become a real phenomenon in Asia Pacific during the last decade. This region has experienced the explosion of bilateral and regional trading arrangements, and is considered as the most progressive and forefront in proliferation of the establishment of Free Trade Agreements (FTAs) and Regional Trade Agreements (RTAs). A report by World Trade Organization in 2010, for instance, shows more than 462 FTAs/RTAs have already established, 111 FTAs/RTAs of those were in Asia Pacific region. The Asia Pacific Economic Cooperation (APEC), as a prominent economic cooperation in region, has actively promoted an economic integration, such the Bogor Declaration in 1994 to achieve free and open trade and investment in Asia Pacific and the idea of establishing Free Trade Area of the Asia Pacific (FTAAP) in 2006, followed by a proposal of using Trans-Pacific Strategic Partnership (TPP) as a pathway of FTAAP in 2009. This article is aimed to address the APECs agenda on this regional economic integration, which generated debates amongst its economies members, scholars and analyst with different perspectives. This writing is also intended to analyze Indonesias position and its strategic policy to response this development.Key words: APEC, regionalism, Asia Pacific